Perbedaan Prevalensi Obesitas antara Etnis Jawa, Tionghoa, dan Arab pada Anak Sekolah Menengah Pertama di Surakarta - Murti, Zenia Purnama; Moelyo, Annang Giri; Widardo, . (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2013)
Background:Obesitycauses many health problems in childhoodsuch ascardiovasculardisease, diabetes, musculoskeletaldisorders, cancersthat causemorbidity and mortalityin adulthood. Ethnicity is a risk factor for obesity. Ethnicity affect eating habits, genetic, amount of energy expenditure, fat distribution and tendency of obese in a child. The aim of this study was to analyze prevalence of obesity in Junior High School Children in Surakarta based on ethnic differences (Javanese, Chinese, and Arabian). Methods:This was a cross-sectional analytic study to 395 students of 8th grade in SMP Negeri 4 Surakarta, SMP Bintang Laut Surakarta, and SMP Diponegoro Surakarta (junior high school) that consist of Javanese, Chinese, and Arabian. Samples were collected by purposive sampling technique. Inclusion criteriaswere students of 8thgrade,parentshave thesameethnicity, and signed an informed consent. Exclusion criterias werechildrenwithedema, have achronicillness, taking medicationlong-termandconditions ofhandicapped.The questionnaire was used to know the ethnic of the child. Body mass index was used to define obesity status with Z-score >+2 SD based onÂ World Health Organization in 2007 growth chart. Data were analyzed by Chi-Square test. Results:This research shows 246 (63%) subjects were Javanese, 79 (20%) subjects were Chinese, and 70 (17%) subjects were Arabian.Â Twenty seven subjects (6.84%) were obese and threehundred andsixty-eight subjects (93.16%) were not obese. Obese prevalence was 4.5 % among Javanese, 8.9 % among Chinese, and 12.9 % among Arabian.It shows a significant differences in the prevalence of obesity among the three ethnics (p=0,036; p < 0.05). Conclusions:There are significant differences in the prevalence of obesity among Javanese, Chinese, and Arabian Ethnic in junior high school children in Surakarta. Keywords:ethnicity, obesity, children